Menara Pendidikan: Elevasi Kesadaran Arsitektural Melalui Program 'Arsitek Mengajar' di SMA Negeri 9 Semarang : Menara Pendidikan: Elevasi Kesadaran Arsitektural Melalui Program 'Arsitek Mengajar' di SMA Negeri 9 Semarang - Djudjun Rusmiatmoko, Djudjun Rusmiatmoko; NURSANTY, EKO; Mawahib, Nughmal; Alwi Asmain, Nabil (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
The 'Architects Teach' initiative at SMA Negeri 9 Semarang represents a pioneering educational endeavor aimed at integrating architectural principles into the high school curriculum. This program seeks to nurture an appreciation and understanding of architectural concepts among students, fostering a deeper connection with their built environment. Through a series of interactive lectures and hands-on workshops, students were introduced to fundamental architectural ideas, encouraging them to observe and critically assess their surroundings. The initiative not only enhanced students' awareness of architectural aesthetics and functionality but also emphasized the importance of sustainable design practices. The program's outcomes suggest a significant shift in students' perceptions of architecture, highlighting the potential of such educational interventions in shaping future generations' engagement with their living spaces. Keywords: Architectural Education, High School Curriculum, Sustainable Design, Student Engagement, Built Environment